Nutritional Fuelling for Microgravity Environment of Space Missions - Chopra, Sneha; Singh, Som N.; Mathur, Pulkit (Current Nutrition & Food Science, 2024)
Since the beginning of space missions, the food systems have undergone a sea change with prolonged manned missions and permanent space habitats. We have a better understanding of physiological changes which happen in humans in space and help in adaptation to the space environment. Yet, much remains underexplored and warrants further research. Space missions today involve a considerable number of individuals operating in a microgravity environment for both short and long periods. The provision of food for such missions and managing the physio-pathological changes that affect nutritional requirements continue to be challenging. Food systems (food and beverages) used during every program to date have been shelf128;stable and were composed primarily of rehydratable or thermostabilized food items. Such foods usually have a lower hedonic value than fresh or frozen foods. Consequently, a reliable food system must provide a wide range of palatable and attractive foods as well as the tools to prepare them (through rehydration, heating, and cooling) to enhance the taste sensation of the crew. Adequate nutrition with easily accessible food is essential to this effort. To deliver nutritional recommendations to crew members for long-duration space missions, it is important to understand how nutritional status and general physiology are linked and affected by microgravity exposure. In view of this, it has been pointed out that nutritional countermeasures could rectify the physiological and behavioural anomalies during microgravity exposure. In this comprehensive narrative review, we have provided an overview of a few recent advances such as silkworm protein, good mood-vegan diet, 3-D food printing, and space garden’s produce for onboard support to food systems. It has also been found that exercise could be an addition to nutritional interventions. Areas of space exploration that require more in-depth research using ground-based bed rest models, as well as inflight microgravity conditions, are highlighted.
Keywords: nutritional countermeasures